Development of 400-μW cryogen-free dilution refrigerators for quantum experiments - Guan, Xiang; Fan, Jie; Bian, Yong-Bo; Cheng, Zhi-Gang; Ji, Zhong-Qing (Chinese physics B, 2024)
We have successfully developed cryogen-free dilution refrigerators with medium cooling power that can be applied to quantum experiments. Breakthroughs have been made in some key technologies and components of heat switches and dilution units. Our prototype has been running continuously and stably for more than 100 hours below 10 mK, with a minimum temperature of 7.6 mK and a cooling power of 450 μW at 100 mK. At the same time, we have also made progress in the application of dilution refrigerators, such as quantum computing, low-temperature detector, and magnet integration. These indicators and test results indicate good prospects for application in physics, astronomy, and quantum information.